2013
DOI: 10.1590/s0100-204x2013000700013
|View full text |Cite
|
Sign up to set email alerts
|

Ethephon use and application timing of abscisic acid for improving color of 'Rubi' table grape

Abstract: -The objective of this work was to evaluate the effect of ethephon and of abscisic acid (ABA) application timing on the color of 'Rubi' Table grape. Eight treatments were evaluated: control, without application; ethephon 500 mg L -1 applied seven days after veraison (7 DAV); and two concentrations of ABA (200 and 400 mg L -1 ) arranged with three application timings at 7 DAV, at 15 days before harvest (DBH), and at 7 DAV + 15 DBH. ABA does not modify physical-chemical characteristics of the cluster and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 7 publications
7
39
0
2
Order By: Relevance
“…The application of ABA did not affect the physical characteristics of other cultivars, including Benitaka, Rubi, and Cabernet Sauvignon (Koyama et al, 2010;Roberto et al, 2012Roberto et al, , 2013. In contrast, for 'Flame Seedless' and 'Redglobe' grapes, in some evaluated crops, there was an increase in berry mass with the application of S-ABA (Peppi et al, 2006(Peppi et al, , 2007a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of ABA did not affect the physical characteristics of other cultivars, including Benitaka, Rubi, and Cabernet Sauvignon (Koyama et al, 2010;Roberto et al, 2012Roberto et al, , 2013. In contrast, for 'Flame Seedless' and 'Redglobe' grapes, in some evaluated crops, there was an increase in berry mass with the application of S-ABA (Peppi et al, 2006(Peppi et al, , 2007a.…”
Section: Resultsmentioning
confidence: 99%
“…bras., Brasília, v.50, n.12, p.1160-1167, dez. 2015 DOI: 10.1590/S0100-204X2015001200005 which emphasizes the importance of developing products with attractive appearance for the food industry (Araújo, 2011;Roberto et al, 2013). Borges et al (2011) and Maia et al (2013) recommend blending 'Isabel Precoce' and 'Isabel' grape juice with a color-rich cultivar, in order to improve juice color.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacampagne et al, (2010) reported a positive impact of ABA on berry colour of grapes. Roberto et al, (2013) found that ABA improved the colour of grapes, especially when applied twice (7 days after veraison + 15 days before harvest) at -1 400 mg l in 'Rubi' table grapes.…”
mentioning
confidence: 96%
“…A partir daí, o efeito do S-aBa foi testado em uvas como 'cabernet Sauvignon', 'Rubi', 'Benitaka' e 'Crimson Seedless', sendo verificado aumento na coloração das bagas (GARDIN et al, 2012;RoBeRto et al, 2012;RoBeRto et al, 2013;Leão et al, 2014;FeRRaRa et al, 2015). Koyama et al (2014a,b) observaram que aplicações exógenas desse regulador na uva 'Isabel' aumentaram a concentração de antocianinas totais nas bagas e nos sucos.…”
Section: Sensory Analysis Of 'Isabel' Grape Juice Submitted To the Apunclassified